Validation of the GAD-7 (Malay Version) among women attending a primary care clinic in Malaysia. - Mohd Sidik, Sherina; Arroll, Bruce; Goodyear-Smith, Felicity (Royal New Zealand College of General Practitioners, 2012)
INTRODUCTION: Anxiety is a common mental health disorder in primary care, with a higher prevalence among women compared to men. AIM: This is the first study to validate the Generalised Anxiety Disorder-7 questionnaire (GAD-7) as a case-finding instrument for anxiety in a primary care setting in Malaysia. The objective was to determine the diagnostic accuracy of the Malay version of the GAD-7 in detecting anxiety among women. METHODS: This cross-sectional study was conducted in a government-funded primary care clinic in Malaysia. Consecutive women participants attending the clinic during data collection were given self-administered questionnaires including the GAD-7 (Malay version). Participants then were selected using systematic weighted random sampling for Composite International Diagnostic Interviews (CIDI). The GAD-7 was validated against the CIDI reference standard. RESULTS: The response rate was 87.5% for the questionnaire completion (895/1023), and 96.8% for diagnostic interviews (151/156). The prevalence of anxiety was 7.8%. The GAD-7 had a sensitivity of 76% (95% CI 61%-87%), a specificity of 94% (88%-97%), positive LR 13.7 (6.2-30.5) and negative LR 0.25 (0.14-0.45). DISCUSSION: The Malay version of the GAD-7 was found to be valid and reliable in case-finding for anxiety in this study. Due to its brevity, it is a suitable case-finding instrument for detecting anxiety in primary care settings in Malaysia.